5(b-1)=7b-5(1+b)

Simple and best practice solution for 5(b-1)=7b-5(1+b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(b-1)=7b-5(1+b) equation:



5(b-1)=7b-5(1+b)
We move all terms to the left:
5(b-1)-(7b-5(1+b))=0
We add all the numbers together, and all the variables
5(b-1)-(7b-5(b+1))=0
We multiply parentheses
5b-(7b-5(b+1))-5=0
We calculate terms in parentheses: -(7b-5(b+1)), so:
7b-5(b+1)
We multiply parentheses
7b-5b-5
We add all the numbers together, and all the variables
2b-5
Back to the equation:
-(2b-5)
We get rid of parentheses
5b-2b+5-5=0
We add all the numbers together, and all the variables
3b=0
b=0/3
b=0

See similar equations:

| 5a+6=a-18 | | |x+8|=C | | 175m-125m+43425=45450-175m | | p-4=-9=p | | 9+6=x-10 | | -2(x+3)+4x=6x+10−2(x+3)+4x=6x+10 | | 2x+3/4(4x+16=7 | | 2x+10-2=-2 | | 2x+4+6x=5x+22 | | -y=-39 | | 4(x-2)-22=-14 | | 3+3x-(x-2)=3x+5 | | 2x+5x-15=13 | | (5/6x+2/3)=-9 | | 4x-146=-8x+94 | | 3/4-y/4=7 | | ((x+4)/2)=((1/3)+(x-1)/2) | | -4+10n=-56 | | x/3=-25 | | -3x-8(x-4)=54 | | 8g+2g–11=9 | | 22+3=4.75x | | Y=3000-(200+0.4y) | | -12x+-9+24x+1=43 | | 3.7+10m=6.12 | | -92+8x=3x+33 | | 12.33=2g+3.63 | | 8t+22–5t=37 | | 64x^2+4x-3=0 | | 2x+1-57=0 | | -11v-3+3v=24 | | {x}{3}=-25 |

Equations solver categories